An Empirical Evaluation of Technology Acceptance Model in Mobile Devices in Healthcare Industry - Kazi, Abdul Kabeer; Jatoi, Amna; Hashmani, Hira (sourcecoder, 2025)
Digital technology is spreading overall industry with a rapid growth, especially in the healthcare industry. Researcher are globally working on different models of technology acceptance but from the initial day technology acceptance was a dilemma for the scientists. This study aims to investigate how patient trust on the healthcare related mobile applications will leads towards their usage and what is the role of the technology acceptance model in this prospective. Primary data was collected from the 345 different patients of Karachi city who are the users of different mobile healthcare applications by a closed ended questionnaire through judgmental sampling. The gathered data was analyzed by using a Partial Least Square approach with SmartPLS software. The result of this study shows that trust is one of the key factors which promotes the usage of the healthcare mobile applications through the technology acceptance model among the patients of Karachi city. Results also shows that the usage of the healthcare related applications are mainly based on how much patients trust the application. More trust in the result and more usage of the application devices. Furthermore it is recommended to the healthcare sector to increase their investment in the area of artificial intelligence to enhance it accordingly.